Chemical compounds associated with increased risk for cancer incidence found in environmental samples obtained from two fire departments - Williams, Denise N.; El Hay, Florencia; Wijesinghe, Arav; Pulluri, Shynitha; Sturdivant, Rodney X.; Barr, Kelli L.; Harris, Debra D. (Frontiers in Materials, 2023)
Firefighters are exposed to many different biological and chemical contaminants while conducting their work duties, including polyaromatic hydrocarbons or PAHs. PAH compounds are of particular interest in investigations of firefighter health as they have been linked to detrimental health outcomes, including respiratory illnesses and cancers, and are found in high concentrations after fires. Thus, they are quantified in several studies on the occupational exposure of firefighters, and they are the focus of several protocols and technologies aiming to mitigate occupational exposures. Fire departments use standard operation protocols for limiting exposure to occupational health hazards, including exposure to chemical compounds such as PAHs. However, observations of firefighter workflows reveal the potential for major contamination of fire station work-live areas. Herein we make an initial report on the PAHs that firefighters continue to be exposed to after they have finished responding to calls and have potentially doffed their protective gear. The sampling of environmental surfaces in fire apparatus and stations was used as data. This study found that PAHs identified on turnout gear were found in the fire station, suggesting that turnout gear may be vectors of toxic chemicals. Therefore, protocols for decontamination of turnout gear and fire stations should be evaluated to remove PAHs and other chemicals known to impair health. This and further surface sampling studies are needed to better understand the full occupational exposures of firefighters to hazardous chemicals.